Characterization and Antioxidant Activity of Mahogany Bark Extract-loaded Chitosan Nanoparticles - Syamsul Falah; Sulistiyani Sulistiyani; Dimas Andrianto (Wood Research Journal, 2012)
Nanoparticles-based drug delivery has been recognized to improve the solubility of poorly water-soluble drugs, prolong the half-life of drug systematic circulation by reducing immunogenicity, and releases drugs at a sustain rate. The present study reports on the characterization of mahogany bark extract-loaded chitosan nanoparticles and their antioxidant activity.  Mahogany bark meal was extracted in boiled water for four hours.  Chitosan-sodium tripolyphosphate (STPP) nanospheres were sonicated with ultrasonicator to obtain chitosan-STTP nanocapsules for 30 and 60 min and then were dried with spray dryer. The chitosan-STPP nanocapsules loaded by mahogany extract were then analysed for surface morphology and physical state by scanning electron microscope (SEM) and X ray diffraction (XRD), respectively. Antioxidant activity of the nanoparticles was evaluated by scavenging the 1,1-diphenyl-2-picrylhydrazyl (DPPH) using free radical method. Based on SEM data, the nanoparticle shapes were viewed to adhere to spherical shape. Spherical chitosan-STTP nanoparticles loaded with mahogany bark extract were obtained in the size range of 480 ~ 2000 nm and 240 ~ 1000 nm for 30 and 60 min of ultrasonication time, respectively. The antioxidant activity of the nanoparticles was lower than that of the native mahogany bark extract.